2013
DOI: 10.1080/09540121.2013.841840
|View full text |Cite
|
Sign up to set email alerts
|

Risk behaviors for HIV in sexual partnerships of San Francisco injection drug users

Abstract: While injection drug users (IDU) in the USA are known to form sexual partnerships with IDU as well as non-IDU, scientific research is lacking regarding risk behaviors for HIV transmission within these partnerships. Such information could aid HIV-prevention efforts among IDU and could also explain the relatively low prevalence of HIV among non-IDU heterosexuals in US cities such as San Francisco. Using data from a cross-sectional sample of San Francisco IDU we estimated (1) the prevalence of IDU-IDU and IDU-non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
4
2
Order By: Relevance
“…The prevalence of high-risk behaviors among our participants was lower than in previous studies. Shared needle use and history of risky sexual encounters were almost mutually exclusive (except for one person), this is vastly different from other studies which found these two behaviors to co-occur (Chen et al, 2014;Damas et al, 2021;Gangi et al, 2020). The history of shared needle use in our study was lower than in other respondentdriven sampling studies on behaviors of PWIDs (Chen et al, 2014;Korthuis et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The prevalence of high-risk behaviors among our participants was lower than in previous studies. Shared needle use and history of risky sexual encounters were almost mutually exclusive (except for one person), this is vastly different from other studies which found these two behaviors to co-occur (Chen et al, 2014;Damas et al, 2021;Gangi et al, 2020). The history of shared needle use in our study was lower than in other respondentdriven sampling studies on behaviors of PWIDs (Chen et al, 2014;Korthuis et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…Shared needle use and history of risky sexual encounters were almost mutually exclusive (except for one person), this is vastly different from other studies which found these two behaviors to co-occur (Chen et al, 2014;Damas et al, 2021;Gangi et al, 2020). The history of shared needle use in our study was lower than in other respondentdriven sampling studies on behaviors of PWIDs (Chen et al, 2014;Korthuis et al, 2012). Considering that there could be a gap between obtaining sterile syringe and actual use (Gangi et al, 2020;Korthuis et al, 2012), access to clean needles among PWIDs in our study could have been close to 100 percent.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Although most previous HIV-risk models have focused on newly diagnosed chronic infection, 10 , 22 24 this represents one of the biggest studies to date to focus on incident HIV infection. 1 , 18 , 25 Although each of the 4 risk behaviors of our final model has been described previously to be associated with HIV infection individually (combination CRAI and 5 or more male partners, 18 , 26 , 27 CRAI with an HIV-positive male, 23 , 28 30 CRAI with a person who injects drugs, 28 , 31 , 32 and self-reported syphilis infection during the last 12 months), 33 , 34 these risk factors have not been described together in a multivariate model. By focusing only on AEH and investigating all of these factors together, we were able to generate a profile for AEH risk among MSM undergoing field-based screening, with an HR of 4.6 for AEH in individuals reporting at least 1 of the 4 risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…For the risk model, we selected 7 binary variables based on simplicity and published epidemiological data that supported inclusion in the predictive model. The variables selected were (1) ≥10 partners within the last year [5,18,19], (2) self-reported bacterial STI during the last 12 months (syphilis, gonorrhea, or chlamydia) [20,21], (3) the combination of condomless receptive anal intercourse (CRAI) and ≥5 male partners [22][23][24], (4) CRAI with an HIV-positive male [9,18,19], (5) CRAI with a person who injects drugs [9,25], (6) injection drug use with shared needles [22,26], and (7) noninjection stimulant drug use (NIDU, defined as use of methamphetamine, ketamine, cocaine, inhaled nitrites, Ecstasy, or GHB) [27,28].…”
Section: Risk Score Developmentmentioning
confidence: 99%